Bridging Cultures through English: A Curriculum for Sustainable Agro-Ecotourism in Higher Education - Chamisah; Aisyah (Jurnal Kolaborasi Akademika, 2026)
The integration of English language education with sustainability-oriented tourism has become increasingly important within higher education, particularly in response to global environmental challenges and the growing demand for sustainable tourism practices. Agro-ecotourism, which combines agricultural activities, ecological conservation, and tourism development, requires graduates who possess not only technical and disciplinary knowledge but also strong intercultural communication and language competencies. In this context, English plays a strategic role as a medium for cross-cultural interaction, knowledge exchange, and sustainability advocacy. This study aims to propose a curriculum framework that bridges cultures through English by integrating sustainable agro-ecotourism principles into higher education learning. Adopting a conceptual and literature-based approach, the article synthesizes key studies on English for Specific Purposes (ESP), intercultural competence, and sustainability-oriented tourism education to inform curriculum design. The proposed framework emphasizes communicative English skills, sustainability literacy, and local cultural engagement as core learning outcomes. The findings indicate that an integrated English-based agro-ecotourism curriculum has the potential to enhance students’ global communication abilities, cultural awareness, and preparedness to contribute meaningfully to sustainable tourism development. This study contributes to curriculum development discourse by offering a theoretically grounded and contextually relevant model suitable for higher education institutions, particularly in developing country contexts.